Isolasi Protoplas secara Enzimatis pada Tanaman Kecipir - Imron Riyadi (Buletin Plasma Nutfah, 2010)
Thekind and concentration of enzyme that appropriate affectedisolation process and result of plant protoplast. The researchwas conducted to enhance the protoplast rendements of wingedbean (Psophocarpus tetragonolobus L.) that was isolated byCellulase RS and Macerozyme R-10 enzyme as single and itscombination in a solution. Concentrations of enzyme usedwere as much as 2.0-3.0% w/v for Cellulase RS and 0.4-0.6%w/v for Macerozyme R-10. The solution containt mannitol 25mM as an osmotycum. Isolation process was done on shakerwith 50 rpm (rotation per minute) speed in dark room for 5hours. Results showed that C3 treatment (concentration ofCellulase RS enzyme as much as 3.0% w/v) resultedprotoplasts density 3.49 x 105 protoplasts/g fresh weight ofhypocotyl and M2 treatment (concentration of Macerozyme R-10 enzyme as much as 0.5% w/v) resulted 3.19 x 105protoplasts/g. Whereas the best combined enzymes treatmentwas achieved by C3M2 (combination between Cellulase RS asmuch as 3.0% and Macerozyme R-10 enzyme as much as 0.5%w/v) which resulted protoplasts density 4.94 x 105protoplasts/g fresh weight of hypocotyl. The protoplast wasintact and viable.